UJI KELARUTAN LOGAM DARI TAILING TIMAH MENGGUNAKAN PELARUT EUTEKTIK BERBASIS KOLIN KLORIDA DAN ASAM p-TOLUENASULFONAT - Nimas Ade Kusdayanti; Winda Rahmalia; Thamrin Usman (Tanjungpura University, 2019)
Deep eutectic solvents (DES) are defined as combinations of two or three components which are able to establish hydrogen bond interactions with each other to form an eutectic mixture, that have a melting point lower than that of the each individual component. This study aims to determine the characteristics of DES based on choline chloride (ChCl) as quaternary ammonium salts and p-toluenasulfonic acid (PTSA) as hydrogen bond donors and to investigate their selectivity for dissolving metals in tin tailings. Synthesis of DES was carried out by mixing ChCl and PTSA with variations of the mole fraction, then stirring at 80 oC for 15 minutes. Resulted products were characterized their freezing point, density, viscosity, conductivity and functional groups. Mixture with a mole fraction of ChCl 0.6 formed homogeny clear liquid. It has a freezing point of 8 oC, density of 1.207 g/mL, viscosity of 4.663 cP, and conductivity of 182.4 mS/cm. Based on fourier transform infrared (FTIR) analysis, the interaction between ChCl and PTSA was due to the formation of hydrogen bonds between the O atoms of PTSA and the H atoms of ChCl. Inductively coupled plasma atomic emission spectroscopy (ICP-AES) analysis showed the presence of 1962 ppm of Fe metal dissolved in DES. This value was significant greater than the presence of other metals in the DES.